How are the Sociolinguistic Competences applied in the English Textbook? - Diyah Nur Hidayati (SALEE: Study of Applied Linguistics and English Education, 2022)
Promoting the sociolinguistic competences in the teaching process is vital since the students are required to use English for real-life communication. One of ways that teachers can do is by inserting sociolinguistic competences in their teaching materials. However, rarely did they focus on the sociolinguistic competences. Therefore, this content analysis research aims to void this gap by analyzing the use of sociolinguistic competences in the textbook entitled “Let’s Talk”. The result shows that the textbook has already applied the sociolinguistic competences in the dialogs including the social factors, speech functions, and Leech’s Politeness Principles (PP). To summarize, textbooks should provide more dialogue models with diverse sociolinguistic contexts for practicing interactional and transactional communication. At that time, the learners would have been exposed to learn effective language use, as well as fluency practice and language accuracy, as these are prerequisites for achieving communicative competence goals.